Establishment of enhanced protein purification strategies for recombinant immunotherapeutics - Shangase, Valentine (Department of Integrative Biomedical Sciences (IBMS), 2025)
Antibody-based diagnostic and therapeutic agents play a substantial role in modern medicine, particularly for cancer management. The use of monoclonal antibodies (mAbs) and their derivatives to fight cancer demonstrates a significant impact on both laboratory research and clinical applications. This is largely attributed to their ability to recognize specific antigens. The enhancement of these well-characterized mAbs with effector molecules with desirable, tailored properties. This further gives the product to homogeneous antibody conjugates and improves their potency while reducing toxic side effects. An efficient and cost-effective protocol to produce high quality recombinant proteins play a pivotal role in supporting both lab-scale research and pharmaceutical applications. Although relying on the limited availability of resources, the MB&I research unit successfully employs a single IMAC step to purify mammalian and bacterially expressed recombinant proteins to successfully supporting a decent number of student projects per year. Such enriched protein preparation does allow preliminary qualitative analysis of such highly active immunotherapeutics; however, expanding this research into future readiness levels needs further expansion. The main objective of this study was to reestablish and develop an improved protein purification strategy by exploring Immobilized Metal Affinity Chromatography (IMAC), Ion Exchange Chromatography (IEX), and Size Exchange Chromatography (SEC) and further strategically integrating these purification techniques to improve protein purity. Intrinsic properties of the proteins of interest, such as the affinity tag incorporated in the recombinant antibody, and its Isoelectric value (pI), largely contribute to the choice of purification technique as demonstrated by the well characterized mammalian-expressed SNAP tag-based antibody fusion protein αASPH(scFv)-SNAP and the bacterially expressed recombinant immunotoxin 13 H22(scFv)-ETA. IMAC was employed as the initial purification step to recover the full-length histidine-tagged recombinant proteins. The Ni2+ immobilized on the matrices in columns has a high affinity for Histidine incorporated, which allows the capture of the target protein. The remaining host proteins were removed by IEX, which excludes charge-based impurity and isolates the target protein. SEC was used as the last polishing step to remove remaining aggregates and contaminants. Each purification strategy was independently enhanced by optimizing purification conditions such as the flow rate and the buffer system and subsequently integrated to achieve improved resolution. The data analysis showed that optimizing running conditions for each purification technique enhanced protein purity. A lower flow rate improved protein retention, thus reducing the loss of target protein. The buffer conditions also played a substantial role in achieving improved protein purity. The integrated purification strategy yielded a higher protein purity compared to the conventional single-step methods. on the contrary, a significant amount of the target protein is lost in each purification technique. An adaptable combinatory chromatography technique was established. The established purification workflow was successfully applied to a variety of other recombinant proteins. This was achieved by careful consideration of the unique physiochemical characteristics of recombinant protein. The established purification techniques can be expanded to a wider variety of fusion proteins. The protein purity and recovery following the application of the combinatory purification technique varied with the combination of chromatography and the nature of the protein. Bacterially expressed proteins require a more expensive wash step compared to mammalian-expressed proteins. However, higher protein yield was obtained from bacterially expressed proteins compared to mammalian-expressed proteins. The findings suggest that the choice of chromatography combination techniques should be based on the nature of the protein, yield, and purity requirement. MSc of Science (Medicine) ValenƟne Amanda Shangase The limited capacity to produce cost-effective recombinant immunotherapeutics significantly restricts the accessibility of antibody-based treatments such as monoclonal antibodies for cancer treatment. This study outlines the technology that can be a baseline for advancing lab-based research and local continuous production of recombinant biopharmaceuticals and offers a great opportunity to close the existing gap in developing countries.